I Told You So! Verbal cue beliefs are associated with truth detection, but not lie detection - Glynis Bogaard; Sarah Elizabeth Fieweger; Ewout H. Meijer (PLoS ONE, 2026)
This study aimed to 1) replicate and extend previous findings on the relationship between accurate beliefs about the diagnosticity of verbal deception cues and actual truth/lie discrimination as reported in Bogaard and Meijer (2017), and 2) examine the role of presentation modality. Participants (N = 246) listed their beliefs about deception cues and then judged the credibility of truthful and deceptive autobiographical statements presented in one of three modalities: audio-only, transcript, or audio-visual. As in the original study, participants provided continuous credibility ratings. In addition, we asked participants to make binary truth/lie judgments, allowing us to assess discrimination accuracy. We replicated the original finding, namely a small but significant positive correlation between accurate verbal cue beliefs and the credibility ratings of truthful, but not deceptive, statements. A small association was also observed between accurate cue beliefs and truth discrimination accuracy. Contrary to our expectations, modality did not significantly influence truth/lie discrimination or credibility judgments. These findings suggest that while cue knowledge may support the recognition of truthful statements, it does not aid in the identification of lies, nor does the presentation format substantially impact veracity judgments.